2020
DOI: 10.3390/pharmacy8040184
|View full text |Cite
|
Sign up to set email alerts
|

Check-In: An Educational Activity to Address Well-Being and Burnout among Pharmacy Students

Abstract: Background: Chronic workplace stress that has not been adequately managed can result in burnout. Healthcare providers; including pharmacists, may be particularly susceptible to this phenomenon, prompting the School of Pharmacy at the University of Waterloo to develop an active-learning activity to teach and reflect on healthcare provider burnout, called Check-In. Methods: Check-In was comprised of a 20 min online lecture on healthcare provider burnout, two pre-readings that highlighted burnout among physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…While the stress remained consistent, it allowed the instructor team to be responsive to student needs throughout the semester. Instructors should consider having a check-in throughout the semester to assess the effectiveness of the course and student well-being which is commonly used in health-related professional fields (Cox-Davenport, 2017;Fernandes et al, 2020). This can happen in conjunction with a mid-semester course evaluation.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…While the stress remained consistent, it allowed the instructor team to be responsive to student needs throughout the semester. Instructors should consider having a check-in throughout the semester to assess the effectiveness of the course and student well-being which is commonly used in health-related professional fields (Cox-Davenport, 2017;Fernandes et al, 2020). This can happen in conjunction with a mid-semester course evaluation.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The University of Waterloo incorporated a single "Check In" activity in a required course that consisted of a background reading, an in-person lecture component, and a faculty-student mentoring session. 21 The investigators found that the 76 (63%) student pharmacists reported the "Check-in" activity as rewarding, and both students and faculty reported it as a positive experience. Finally, 49 (36%) first-year student pharmacists at one school of pharmacy wrote reflections on personal well-being in one of the required courses in the curriculum.…”
Section: A J P Ementioning
confidence: 99%
“…[11][12][13] Based on the 2017-2018 American Association of Colleges of Pharmacy (AACP) Student Affairs Standing Committee's charge to identify best practices to promote student well-being and resilience and the adoption of "Achieving Well-being for All" as one of AACP's 2021-2024 strategic priorities, there has been an impetus for pharmacy educators to evaluate strategies that promote student well-being and reduce burnout. [14][15][16][17][18][19][20] Since much of student well-being has been focused during the pharmacy didactic curriculum, we developed the Well-being Promotion (WelPro) Program at the University of California, San Francisco (UCSF) School of Pharmacy to reduce burnout and promote well-being among Advanced Pharmacy Practice Experience (APPE) students. WelPro centers around three major wellness pillars: self-management strategies, critical reflection (CR), and community building.…”
Section: Introductionmentioning
confidence: 99%